Scratch Property of Polyurethane Nanocomposites Studied by Nanoindentation - K., Yusoh (Asian Research Publishing Network (ARPN), 2016)
Nanoindentation technique have been used extensively to measure the nanomechanical properties of thin films. However, the determination of the surface mechanical properties such as scratch behavior using this technique is relatively new. In this work, the scratch property of polyurethane nanocomposites was studied and proposed. A series of polyurethanegraphite oxide (GO) and polyurethane carbon nanotubes (single-walled (SWNT) and multi-walled carbon nanotubes(MWNT)) were prepared by in situ polymerization. It is believed that the preparation of polymer/GO or polymer/CNTs nanocomposites with homogeneous dispersion of nanofillers in the matrices is a crucial step to developing highperformance polymer nanocomposites. The results pronounced that with incorporation of nanofillers (GO and CNTs) the scratch depth of polyurethane matrix was dramatically reduced. With only 4wt% of GO the PU nanocomposites had greater hardness and showed better scratch resistance. In addition, the scratch penetration was less for PU-SWCNT composites than for the PU-MWCNT composites and it demonstrated as the time to achieve the maximum depth increased.